การแยกโมเลกุลลำดับส่วนไคโตซานจากการฉายรังสีแกมมา โดยใช้วิธีเลือกการตกตะกอนด้วยตัวทำละลายที่เหมาะสม - วรรณวิมล ปาสาณพันธ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The objective of this research was to study the suitable conditions for molecular weight fractionation of gamma radiation degraded chitosan by selective precipitation using suitable solvents to obtain chitosan with Mv of 40,000 and 8,000 Da. The degradation of chitosan sample was performed by successive gamma irradiation of chitosan powder with radiation dose of 60 kGy and 10%(w/v) of the irradiated chitosan in 2.5% acetic acid with radiation dose of 30 and 110 kGy for prepared chitosan with Mv of 40,000 and 8,000 Da, respective y. Using 1%NaOH for the selective precipitation. The results from the research indicated that the suitable conditions for the precipitation of chitosan with Mv of 40,000 Da. by the 1st fractionation of chitosan sample : distilled water : 1%NaOH (20:50:10 ml.). Let it steady about 1 hr. for precipitation and then seperateted the fraction and adding 1%NaOH 20 ml.(1hr.) in the seperated solution for the 2nd fractionation to obtain the 2nd precipitate with Mv of 42,835 (%58.40%yield). For Mv of 8,000 Da., the fraction is 40:100:50 ml.(1day) for 1st fractionation and then adding 1%NaOH 40 ml.(10days) in the seperated solution far the 2nd fractionation to obtain the 2nd precipitate with Mv of 7,915 Da.(6.20%yield).